Blood clot formation in reinfusion bag with CATSmart: Two case reports. Issue 11 (November 2019) - Kim, Jun Hyun; Bae, Ja Young; Lee, Sang Il; Heo, Min Hee; Kim, Kyung Tae; Park, Jang Su; Kim, Ji Yeon
Autologous blood cell salvage reduces the need for postoperative allogeneic blood transfusion and alleviates immunologic reactions, so the technique is commonly used in cardiac surgery. The continuous autotransfusion system is a type of blood cell salvage device. Although the processing program of continuous autotransfusion system includes filtering of several materials from suctioned blood, such as clots, leukocytes, cytokines, and complement, we identified some unexpected blood clots in the reinfusion bag. Pathologic examination revealed that the clots were composed of fibrin, red blood cell aggregates, and histiocytes. We report two cases of these abnormal findings during the use of CATSmart in cardiac surgery.